PENGARUH PELAKNASANAAN SUPERVISI AKADEMIK TERHADAP PENINGKATAN KINERJA GURU DALAM PROSES PEMBELAJARAN - Sariakin, Sariakin; Yulsafli, Yulsafli; Rahmattullah, Rahmattullah (LPPM Institut Pendidikan Nusantara Global, 2023)
The aim of this research is to determine the effect of implementing academic supervision on improving the performance of high school teachers in Subulussalam City in teaching. This type of research is experimental research with a pre-test and post-test design. The population in this study were all SMAN teachers in Subulussalam City, totaling 268 people. Meanwhile, the sample in this study consisted of 20 teachers whose performance was still low. The sampling technique is purposive sampling. The instrument used to determine teacher performance in implementing the learning process is in the form of a questionnaire. The data analysis technique uses the Wilcoxon test. The research results show that the implementation of academic supervision has an effect on improving teacher performance in implementing the learning process. This is illustrated by the results of the Wilcoxon Test which was carried out with the result obtained Jcount = 0. With α = 0.05 and n=20, then based on the list, Jtable = 52. From these data it can be seen that Jcount is smaller than the Jtable value, so Ho is rejected. This is reinforced by the Z formula equation. Because the calculated z value is -2.803 and this value is smaller than the table z value, namely -1.96. Therefore, Ho is rejected so that the teacher's performance in implementing the learning process increases after being given academic supervision.